Taxonomic revision of the species of Stenothemus from Southwest China (Coleoptera, Cantharidae), with the descriptions of five new species - Yang, Yuxia; Ge, Shujuan; Yang, Xingke; Liu, Haoyu (European Journal of Taxonomy, 2021)
The species of Stenothemus Bourgeois, 1907 from Southwest China are reviewed. Three species are transferred to this genus, S. davidi (Pic, 1926) comb. nov. (from Malthacus Kirby, 1837), S. minutissimus (Pic, 1933) comb. nov. (from Micropodabrus Pic, 1920) and S. singularicollis (Pic, 1933) comb. nov. (from Lycocerus Gorham, 1895). Two new synonyms are suggested, S. dinshuiensis Švihla, 2011 syn. nov. is synonymized with S. davidi and S. melleus Švihla, 2005 syn. nov. with S. singularicollis. Stenothemus shaanxiensis Švihla, 2004 stat. nov. is raised to species level from a subspecies of S. benesi Švihla, 2004. Five new species are described, S. gracilis Y. Yang & X. Yang sp. nov., S. chongqingensis Y. Yang & H. Liu sp. nov., S. flavicollis Y. Yang & S. Ge sp. nov., S. jindraimimus Y. Yang & X. Yang sp. nov. and S. laticornis Y. Yang & H. Liu sp. nov., which are illustrated with photographs of habitus, aedeagi, abdominal sternites VIII and internal genitalia of the female. Characters of the female reproductive system are described for the first time for the following species: S. diffusus Wittmer, 1974, S. dundai Švihla, 2004, S. grahami Wittmer, 1974, S. jindrai Švihla, 2004, S. tryznai Švihla, 2004 and S. singularicollis. Some additional distribution information is added for previously known species. A key for the identification of all studied species is provided.